The Influence of the Avicennan Theory of Science on Philosophical Sufism: The Concept of the Divine Science in Qūnawī and Fanārī - Daşdemir, Yusuf (Oriens, 2020)
Abstract This article discusses the application of the Avicennan theory of demonstrative science on taṣawwuf, or the Divine Science (al-ʿilm al-ilāhī), by members of the Akbarian tradition, particularly Ibn ʿArabī’s (d. 1240) stepson and most influential disciple, Ṣadr al-Dīn al-Qūnawī (d. 1274), and his commentators, among whom the most prominent was Mullā Muḥammad b. Ḥamza al-Fanārī (d. 1431). It aims to find out what kind of relationship was developed between Avicennan logic and Sufism by the two members of the Akbarian school in the post-classical Islamic thought. It also seeks to show that the convergence between different currents of Islamic thought—Sufism and philosophy in this case—led to some adaptation problems and internal inconsistencies for these currents.